Peran ASEAN Agreement on Disaster Management and Emergency Response (AADMER) dalam Penanggulangan Bencana Alam di Indonesia - Agussalim Burhanuddin; Adis Dwi Magfirah; Indra; Nandito Octaviano Guntur; Kezia Atirah Monica Bubun; Muhammad Daffa Rizqilah; Annisa Apriliani (Hasanuddin Journal of International Affairs, 2022)
Responding to problems related to natural disasters, ASEAN created a regional regime, namely AADMER (ASEAN Agreement on Disaster Management and Emergency Response) which was framed based on the commitment of “One ASEAN, One Response”. The research method that will be used is descriptive qualitative method. Primary data were obtained from in-depth interviews with a scientist who has a special concern about ASEAN disaster management. Then, the primary data was confirmed and clarified with secondary data obtained from the literature, especially journals, the ASEAN framework, and Indonesian law related to disaster management. From this study it was found that the Indonesian government had taken sides with the Indonesian government to adopt AADMER through the National Disaster Management Agency (BNPB). Due to the limitations of ASEAN's work, member countries can realize AADMER. Similarly, Indonesia's inadequacy in threat management is examined. The efficacy of disaster risk reduction is noteworthy as a regional organization has the ability to expand its authority in making regional arrangements to address the issue.   Menyikapi permasalahan permasalahan terkait bencana alam, ASEAN menciptakan rezim regional yaitu AADMER (ASEAN Agreement on Disaster Management and Emergency Response) yang dibingkai berdasarkan komitmen “One ASEAN, One Response”. Metode penelitian yang akan digunakan adalah metode deskriptif kualitatif. Data primer diperoleh dari wawancara mendalam dengan seorang akademisi yang memiliki perhatian khusus seputar penanganan bencana ASEAN. Kemudian, data primer dikonfirmasi dan diklarifikasi dengan data sekunder yang diperoleh dari tinjauan literatur khususnya jurnal, kerangka ASEAN, dan hukum Indonesia terkait penanggulangan bencana. Dari penelitian ini ditemukan bahwa keberpihakan Indonesia telah dilakukan oleh Pemerintah Indonesia untuk menganut AADMER melalui Badan Nasional Penanggulangan Bencana (BNPB). Karena keterbatasan kerja ASEAN, negara-negara anggota dapat menghambat pemenuhan AADMER. Demikian pula, ketidakcukupan Indonesia dalam manajemen risiko bencana diperiksa. Kemanjuran pengurangan risiko bencana patut dicatat sebagai organisasi regional yang memiliki kemampuan untuk memperluas kewenangannya dalam membuat pengaturan regional untuk mengatasi masalah tersebut.